Combined metagenomic and metabolomic analyses reveal gut microbiota dysbiosis and metabolic dysfunction in pediatric neurodevelopmental disorders - Wang, Qi; Luo, Yuanhao; Mao, Chunmei; Xiang, Xuesong; Chen, Juanjuan (Frontiers in Immunology, 2025)
IntroductionNeurodevelopmental disorders (NDDs) are chronic brain diseases linked to innate immune signaling abnormalities, affecting children with complex gut-brain axis etiologies and limited targeted therapies. While infant microbes/metabolites may predict childhood NDDs, their landscape and host-metabolism interactions in NDDchildren remain unclear.MethodsThis study enrolled 40 NDDchildren (mean age: 5.18 ± 1.77, F:M = 11:29) and 60 healthy controls (HCs; mean age:5.11 ± 1.42, F:M = 25:35) from Gansu Province Hospital Rehabilitation Center. Shotgun metagenomics and untargeted metabolomics was used to analyze gut microbiota and fecal/plasma metabolites, multi-omics integration analysis was performed to explore host-microbe interactions.ResultsClinically, NDD children showed self-care, concentration, and social behavior deficits, with grandparents as primary caregivers, versus parents in HCs. Microbiome analysis revealed reduced gut diversity and dysregulation in NDDs: depleted beneficial taxa including Akkermansia muciniphila and Lactococcus lactis, but enriched GABA/lactateproducing bacteria; and disrupted pathways included polysaccharides/fatty acids/amino acid/purine ribonucleosides metabolism. Fecal metabolomics identified 100 enriched metabolites including polyamines and GABA in 45 pathways and 254 depleted metabolites including bile acids and butyrate in 57 pathways. Plasma metabolomics showed 321 enriched metabolites like free fatty acids in 143 pathways and 270 depleted metabolites including glycerophospholipids in 84 pathways. Notably, phenolic acids, arginine/proline metabolism, and HIF-1 signaling were enriched in both feces and plasma of NDDs children. Benzene derivatives, indoles, steroid hormone biosynthesis, and tryptophan/tyrosine/phenylalanine metabolism were increased in plasma but decreased in feces, while oxidized lipids, amino acids and derivatives, metabolism of glycine/serine/threonine, alanine/aspartate/glutamate, and cysteine/methionine showed the opposite pattern. Venn analysis identified 29 common metabolites, with eight in KEGG maps. 11-dehydrocorticosterone, LPC (17:0/0:0), adipic acid, and sucralose were decreased in feces but increased in plasma; 1-methylhistidine and trigonelline were decreased in both; L-asparagine anhydrous was increased in feces but decreased in plasma; and sarcosine increased in both. Microbe-metabolite correlation analyses linked these metabolites to NDDs depleted species A. muciniphila, L. lactis, A. butyriciproducens, and etc.DiscussionsCollectively, our study presents the first integrated profile of gut microbiome, microbial metabolites, and host metabolome, reveals gut microbiota dysbiosis, functional impairment, and metabolic disturbance in pediatric NDDs. These findings provide a theoretical foundation for microbiotaand metabolite-targeted therapeutic strategies in childhood NDDs.